Quality and cost in production management process - Rosu, Magdalena (Strojniški vestnik, 2008)
The paper presents an overview of the approaches usually used in production process, specific in planning and control. The goal is to supply "the big picture" of the methods and techniques often met in the entire production process, including the planning and control phases. Thus, some important concepts and techniques like Six Sigma, Concurrent Engineering (CE), Quality Function Deployment (QFD), Enterprise Resource Planning (ERP) and Reverse Engineering (RE) are briefly described, together with techniques and methods for reducing the value of the lead time. The description is sustained by diagrams showing the flow of the activities involved in each method.
Keywords: proizvodni procesi; vodenje proizvodnje; metode